2004
DOI: 10.1007/s00134-003-2048-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects on skeletal muscle of intravenous glutamine supplementation to ICU patients

Abstract: Intravenous glutamine supplementation to ICU patients for a period of five days resulted in normalization of plasma glutamine concentrations in a dose-dependent way whereas muscle glutamine concentrations were unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 30 publications
6
76
1
6
Order By: Relevance
“…Lower-dose glutamine Brantley & Pierce (12) Déchelotte et al (15) Fuentes-Orozco et al (18) Griffiths et al (21) Hall et al (22) Jones et al (25) Kumar et al (27) Luo et al (28) Ockenga et al (33) Perez-Barcena et al (36) Sahin et al (38) Tjäder et al (41) Wischmeyer et al (42) Subtotal ( (P=0·11) 14 1 2 2 11 4 0 10 47 32 22 21 72 41 10 59 304 9 6 5 10 21 3 2 4 37 31 22 24 72 39 10 64 299 1·32 0·13 0·34 0·15 0·44 1·30 0·16 3·06 0·66 0·50, 3·51 0·02, 1·19 0·06, 1·98 0·03, 0·78 0·19, 0·99 0·27, 6·21 0·01, 3·85 0·90, Categorisation into critical illness or surgical trials was difficult. Trials in which participants had pancreatitis or surgery followed by complications, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Lower-dose glutamine Brantley & Pierce (12) Déchelotte et al (15) Fuentes-Orozco et al (18) Griffiths et al (21) Hall et al (22) Jones et al (25) Kumar et al (27) Luo et al (28) Ockenga et al (33) Perez-Barcena et al (36) Sahin et al (38) Tjäder et al (41) Wischmeyer et al (42) Subtotal ( (P=0·11) 14 1 2 2 11 4 0 10 47 32 22 21 72 41 10 59 304 9 6 5 10 21 3 2 4 37 31 22 24 72 39 10 64 299 1·32 0·13 0·34 0·15 0·44 1·30 0·16 3·06 0·66 0·50, 3·51 0·02, 1·19 0·06, 1·98 0·03, 0·78 0·19, 0·99 0·27, 6·21 0·01, 3·85 0·90, Categorisation into critical illness or surgical trials was difficult. Trials in which participants had pancreatitis or surgery followed by complications, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When determining the target for dosing of exogenous glutamine supplementation, small studies of intravenous supplementation restoring hypoglutaminemia back to normoglutaminemia are usually cited [8], [9]. Th ese data have also been applied to enteral administration of supplementation, although enteral doses only marginally aff ect plasma concentration [10]- [12].…”
Section: Targets For Supplementationmentioning
confidence: 99%
“…Moreover, with a high rate of intravenous glutamine infusion, a steady state will be reached [8], [9]. Th e suggested relationship between a high plasma glutamine concentration at admission and an unfavorable outcome is based on a very limited number of observations, and needs to be further explored by observational studies.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…CIP manifests especially with the weakness of the respiratory muscles, leading to problems in weaning from mechanical ventilation in the intensive care unit (Tennila et al 2000). A prospective randomizing study in ICU patients using different doses of parenteral glutamine evaluated their effects on muscle (Tjäder et al 2004) and showed that, in spite of all Gln doses being able to normalize plasma glutamine concentrations, Gln did not attenuate the depletion of muscle free glutamine frequently observed in ICU patients. Therefore, glutamine administration may not affect skeletal muscle turnover.…”
Section: Clinical Studiesmentioning
confidence: 99%